Efek Balance Exercise Terhadap Kemampuan Keseimbangan Lansia Post Stroke Non-Hemoragic: Case Report - Fajar Mulyanto; Wahyuni Wahyuni; Taufiq Anwar; Farid Rahman (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Stroke causes balance disorders including muscle weakness, decreased soft tissue flexibility, as well as motor and sensory control disorders, causing sufferers to be prone to falls. To reduce balance disorders, balance exercises can be given which aim to increase lower extremity muscle strength and body balance. Objective: To determine the effect of balance exercise on the ability to balance and the risk of falling in stroke patients. Methods: Using single-subject research conducted on the elderly post stroke non- hemoragic by being given balance exercise 3 times in 3 weeks, then evaluation measurements were carried out using the Time Up and Go Test (TUGT) and Berg Balance Scale (BBS). Results: The results showed that the subject experienced an increase in walking speed in doing the TUGT test. As for the evaluation measurement using the BBS, the subject did not experience an increase in the BBS score. Conclusion: Balance exercise 3 times for 3 weeks increases the ability to balance the body and self-confidence in the elderly subjects post stroke non-hemoragic.Keywords: balance exercise, balance, elderly, fall risk, stroke